Competency-Based Human Resource Management Practice PT. BPJ - Anggara, Firman; Soeling, Pantius Drahen (International Journal of Social Service and Research, 2023)
The economic crisis ready to hit the company at any time makes every company always on standby, so the development of human resources is important to survive. The better the human resources owned by a company, the longer the company will be able to survive. This study aims to determine competency-based human resource practices with case studies of PT. BPJ. This research uses qualitative research with a case study approach. The study's results found that competency-based human resource management practices are contained in four activities related to human resources: recruitment and selection, training and development, and career management. The implementation of human resource management is implemented in it to get employees who have good performance and can improve the company's quality.